2021
DOI: 10.1016/j.jclinepi.2020.09.029
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review finds Core Outcome Set uptake varies widely across different areas of health

Abstract: The aim of our review was to bring together studies that had assessed the uptake of core outcome sets (COS) to explore the level of uptake across different COS and areas of health. Study Design and Setting: We examined the citations of 337 COS reports to identify studies that had assessed the uptake of a particular COS in randomized controlled trials (RCTs) or systematic reviews (SRs). Results: We identified 24 studies that had assessed uptake in RCTs and two studies that had assessed uptake in SRs. The studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…However, the clinical trials editorial team have, at times, observed either partial or absent COS utilization and reporting in submitted clinical trial manuscripts, despite the existence of a published COS in that field. This observation is supported by the findings of a recent systematic review examining COS uptake, which demonstrated high variability, ranging from zero uptake in trials for gout to 82% for rheumatoid arthritis, with uptake of a full COS typically found in fewer than 25% of trials 6 …”
Section: Barriers (Hughes Et Al)6 Interventions (Home Roadmap)13supporting
confidence: 59%
“…However, the clinical trials editorial team have, at times, observed either partial or absent COS utilization and reporting in submitted clinical trial manuscripts, despite the existence of a published COS in that field. This observation is supported by the findings of a recent systematic review examining COS uptake, which demonstrated high variability, ranging from zero uptake in trials for gout to 82% for rheumatoid arthritis, with uptake of a full COS typically found in fewer than 25% of trials 6 …”
Section: Barriers (Hughes Et Al)6 Interventions (Home Roadmap)13supporting
confidence: 59%
“…Third, the use of a range of metrics may impede communication between clinicians and consumers, making shared decision-making more difficult. The review here is consonant with calls in the field to develop common metrics 264 , to agree on core outcome sets 265,266 , and to harmonize measurement results 263 .…”
Section: Discussionmentioning
confidence: 71%
“…One area in which COS uptake has been well examined to date is rheumatoid arthritis, with uptake of rheumatoid arthritis COS within clinical trials increasing over time 12,22 . Across other areas of health and healthcare research, COS uptake in trials is unclear 23 . Use of COS, or not, may be attributable to trialists' perceptions of the relevance and scope of a particular COS for use in a trial 24 .…”
Section: Development and Use Of Cos Is Supported By The Core Outcome Measures In Effectiveness Trialsmentioning
confidence: 99%